Interface design for automation of the scanning EMG method [Taramali EMG yönteminin otomasyonu için arayüz tasarimi] - (:unkn) unknown (My University, 2009)
Scanning EMG is a method developed for examining the electro-physiological cross section and the size of the motor unit of a human muscle. Electrical specifications of the motor unit can be obtained as well as anatomical distribution of muscle fibers and pathological changes between different muscles can be examined by the help of this method. In this paper; an automation system which is designed for the execution of scanning EMG method, whether manually or automatically, and a user-interface are described. Parameters like step count and step size which are about the movement of an electrode, moved by a linear actuator, through muscle fibers can be defined as reference by user via designed interface. As a result, acquired signals are digitalized by data-acquisition card (DAQ) and saved as text file for the future signal process tasks. ©2009 IEEE.